Preparação e incorporação do substrato em atta sexdens rubropilosa forel, 1908 (Hymenoptera: formicidae) e morfofuncionalidade mandibular em espécies de atta - Silva, Laís Cristina da [UNESP] (2014)
Species of leaf - c utting ants of the genus Atta are important pests of agriculture and forestry Brazilian because they use plant material as substrate for the cultivation of your symbiotic fungus, thus requiring control methods to reduce the damage caused by their foraging activities. The most used are the toxic baits. The symbiotic association provides adequate nutritional constitution to the colony, the main food source for the larvae and important constituent of the diet of adult workers. The objectives of this study was observe the behavioral repertoire of Atta leaf cutter during preparation and incorporation of two different substrates, leaves and ant poison baits, as well as the participation of each caste involved in this process, stressing possible morphological diffe rences between the jaws of leaf - cutting ants grasses and dicots. For a detailed description of both jaws of the workers, anatomy and chemical composition of plant material species foraged by bisphaerica Atta and A. s. rubropilosa was prepared, as well as a n ethogram showing behavioral acts performed by workers' overalls, and generalist foragers of A. s. rubropilosa during processing and incorporation of two different substrates. It has verified that Atta species have similar morphology jaw. The difference w as observed just inside the grapes analyzed. Regarding the morphological description of the plant material foraged, results indicate that grasses have more lignified points, it can be inferred that their foraging and processing requires a greater effort of workers and could lead to differentiation in behavioral acts in their preparation and incorporation into the fungus garden . For the three castes found eight behavioral acts were recorded, regardless of substrate processed by workers ...